2020
DOI: 10.1097/pts.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Rescue Deteriorating Patients: A Systematic Review of Root Causes and Improvement Strategies

Abstract: Objectives: "Failure to rescue" (FTR) is the failure to prevent a death resulting from a complication of medical care or from a complication of underlying illness or surgery. There is a growing body of evidence that identifies causes and interventions that may improve institutional FTR rates. Why do patients "fail to rescue" after complications in hospital? What clinically relevant interventions have been shown to improve organizational fail to rescue rates? Can successful rescue methods be classified into a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 84 publications
(147 reference statements)
4
102
0
1
Order By: Relevance
“…We also found that PPE restrictions were limiting the amount of face-to-face contact they were able to have with patients, which again represents the loss of a vital source of patient information. Failure to recognize deteriorating patients has been highlighted in the literature as one of the leading causes of poor patient outcomes when they are hospitalized, and leads to significantly higher morbidity and mortality due to delays in provision of timely and appropriate care [1][2][3][4][5]. This is particularly true during pandemics, as the experienced nurses interviewed in the current study highlighted the importance of recognizing rapidly deteriorating COVID patients in being able to effectively treat them.…”
Section: Plos Onementioning
confidence: 73%
See 1 more Smart Citation
“…We also found that PPE restrictions were limiting the amount of face-to-face contact they were able to have with patients, which again represents the loss of a vital source of patient information. Failure to recognize deteriorating patients has been highlighted in the literature as one of the leading causes of poor patient outcomes when they are hospitalized, and leads to significantly higher morbidity and mortality due to delays in provision of timely and appropriate care [1][2][3][4][5]. This is particularly true during pandemics, as the experienced nurses interviewed in the current study highlighted the importance of recognizing rapidly deteriorating COVID patients in being able to effectively treat them.…”
Section: Plos Onementioning
confidence: 73%
“…In hospital settings, the failure to identify deteriorating patients can lead to delays in appropriate patient care [1][2][3], which can cause increased morbidity and mortality [4,5]. A recent qualitative study of surgical intensive care unit (ICU) nurses found that their ability to quickly identify deteriorating patients led to the early deployment of the rapid response team [6].…”
Section: Introductionmentioning
confidence: 99%
“…Failure to rescue (FTR) -the failure to prevent patient deterioration and death after complications of medical care or underlying illness -is also a growing area of attention in patient safety 24 that creates opportunities to improve identification of potential need for rescue as well as ways to respond more quickly and successfully to minimize risk. Barriers to timely rescue include inadequate staffing levels and education, lack of early warning systems and detection of deteriorating patients, communication barriers between patients and providers, lack of effective handoff communication, and poor institutional ability to respond to the deteriorating patient.…”
Section: Safety Outside the Ormentioning
confidence: 99%
“…Barriers to timely rescue include inadequate staffing levels and education, lack of early warning systems and detection of deteriorating patients, communication barriers between patients and providers, lack of effective handoff communication, and poor institutional ability to respond to the deteriorating patient. 24 Further work must be done to identify and implement evidence-based strategies and interventions to combat FTR. This includes efforts to create and disseminate early warning systems for all perioperative patients as well as develop effective electronic warning systems.…”
Section: Safety Outside the Ormentioning
confidence: 99%
“…This could include awareness of physical deterioration in the patient's condition where the nurse would be expected to identify changes in vital observations. Analysis of failure to rescue deteriorating patient events (Burke et al, 2020) reveals that nurses may fail to recognise patient deterioration because of workload, fatigue, distractions and cognitive overload. Such failings can be attributed to reduced situational awareness.…”
Section: Key Conceptsmentioning
confidence: 99%